Exposure to different types of mass media and timing of antenatal care initiation: insights from the 2016 Uganda Demographic and Health Survey - Quraish Sserwanja; Linet M. Mutisya; Milton W. Musaba (BMC, 2022)
Abstract Background Early initiation of antenatal care (ANC) within the first trimester is highly recommended in the current 2016 World Health Organization (WHO) guidelines. Mass media has the potential to promote early initiation of ANC because it has been used successfully in several programs. However, there is paucity of literature on the effect of exposure to different types of media on the timing of ANC initiation in Uganda. Our study aimed at exploring associations between exposure to different types of mass media and timing of ANC initiation among women in Uganda. Methods We used a cross sectional study design, to conduct a secondary analysis of data collected in the 2016 Uganda Demographic and Health Survey (UDHS). We included weighted data of all the 10,152 women of reproductive age (15-49 years). Multistage stratified sampling was used to select study participants. Multivariable logistic regression was used to determine the association between exposure to different types of mass media and early initiation of ANC. Results Almost a third of the women (2953/10,152, 29.1%, 95% CI 27.9-29.6) initiated their first ANC contact in the first trimester. Women who listened to radio at least once a week (adjusted OR (aOR 1.14, 95% CI 1.01-1.30) and those who watched television less than once a week (aOR 1.28, 95% CI 1.07-1.53) had higher odds of initiating ANC earlier compared to their counterparts not exposed to radio and television respectively. Conclusion Exposure to radio and television is associated with timing of ANC initiation in Uganda. Importantly, the two types of mass media have the potential to reach women with low levels of education and encourage them to utilize maternal health services. The Ugandan government needs to prioritize and intensify the use of radio and television to promote the benefits associated with timing of ANC initiation.